Guest workers: Adequate incentives for voluntary return - Slobodan Djajić; Alexandra Vinogradova (Graduate Institute of International and Development Studies, 2013)
A guest-worker program can be a very flexible and convenient way of meeting labor shortages in a host country, assuming that the migrants obey the rules. This paper investigates the conditions under which guest workers have sufficient incentives for voluntary return to their country of origin when their work permits expire. The analysis is conducted in the context of a lenient enforcement regime that avoids deportations of undocumented aliens. It relies instead on eligibility criteria and pricing instruments, such as partial withholding of salary and an exit tax for those who overstay, to provide adequate incentives for voluntary return at the end of the contract period.
Keywords: F22; 330; temporary migration; overstaying; voluntary return; guest workers